Zinc supplementation in pregnancy and its relation to chronic non-communicable diseases (Research, Society and Development, 2022)
Objective: Evaluate zinc supplementation during pregnancy as a way to prevent the onset of chronic non-communicable diseases (NCDs) in the adult phase of offspring. Method: This research was a literature review with a quantitative approach, Medline, Scielo, PubMed and Google Scholar. The research was carried out in Portuguese, in the period between 2000 and 2018, using the following descriptors: CNCD, pregnancy, zinc, fetal programming, supplementation during pregnancy. Results: Zinc supplementation during pregnancy is beneficial for both the mother and the fetus, considering that this nutrient is involved in important biochemical, immunological, clinical and metabolic processes. Conclusion: From the results of the research, it was possible to conclude that, indirectly, zinc supplementation during pregnancy can prevent the onset of chronic non-communicable diseases (NCDs) in the adult phase of the offspring.